Assuring learning and teaching standards through inter-institutional peer review and moderation : a user guide and handbook. - Krause, Kerri-Lee; Scott, Geoff; Aubin, Kate; Alexander, Heather; Angelo, Tom; Campbell, Stuart; Carroll, Martin; Deane, Elizabeth; Nulty, Duncan; Pattison, Pip; Probert, Belinda; Sachs, Judyth; et al. (Australia. Office for Learning and Teaching, 2014)
This User Guide and Handbook is an outcome of a project funded by the Office for Learning and Teaching (OLT) entitled 'A sector-wide model for assuring final year subject and program achievement standards through inter-university moderation'. This project addressed the Tertiary Education Quality and Standards Agency (TEQSA) imperative to demonstrate sector-level, self-regulated, robust approaches for assuring quality and standards and highlighted the role of peer review. The project tested an inter-institutional blind peer review methodology using a broad, representative range of university partners. In the approach, groups of academics teaching equivalent units of study in two partner universities undertook a blind review of both the assessment inputs (subject outlines, assessment tasks and marking criteria) and assessment outcomes (de-identified samples of assessment at different grade levels) from a partner university teaching a similar final year subject. The project developed a validated, robust approach for assuring subject achievement standards through inter-university moderation in common final year subjects across disciplines. The findings show that there is broad agreement among peer reviewers from a range of university types on disciplinary teaching and learning standards, particularly in judgements about threshold Pass/Fail grades. Other outcomes of the project include: a full report; a peer review template; a sample policy for inter-institutional peer review; guidelines for local responses to peer reviewer discrepancies; strategies for publishing selected inter-institutional peer review outcomes; and recommendations for national and institutional policy and practice. [About the project, Full Report abstract, ed]